“Factores de empleabilidad del talento Senior en Ecuador’’. - Feijoó Montoya, Julissa Mishel (2024)
The objective of this research was to validate the "Employability Factors Scale" for senior talent in the Ecuadorian context. The Spanish scale elaborated by Martinez et. al (2021), originally with 44 items and 9 factors, was initially applied to a sample of 172 people over 50 years of age in Ecuador. The data were subjected to a validation process including exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The EFA revealed a structure of three essential factors: personal conditions/characteristics, training/job skills and job search. This new structure emerged from the analysis of the Ecuadorian data, preserving the core of the instrument and responding to local needs. The AFC presented a slightly high RMSEA of 0.090, but satisfactory indices such as CFI=0.861 and TLI=0.854, confirming the adequacy of the model. Other indicators were evaluated as high factor loadings above 0.60 in the AFE, demonstrating construct validity and adequate reliability. The new validated scale constitutes a culturally relevant tool for assessing the employability of senior talent in Ecuador, allowing a solid interpretation of the underlying factors. Although limitations were identified in the sample size, it is recommended to expand it, investigate cultural nuances and apply it in studies on the employability of this age group, contributing to the design of public policies that promote an active professional life and a better economic situation.